Understand science - Evans, Jon, 1972- ([Place of publication not identified] : McGraw-Hill, [Place of publication not identified] : McGraw-Hill, 2011)
Covers all of the essential facts on all key areas from evolution and cell biology to star formation and plate tectonics. The essential introductory guide for a journey of discovery through physics, chemistry, biology, and more.
How we got here. Bang, we're off ; Molecules in space ; Recipe for a solar system ; Life begins ; Evolution and extinction -- Way of all flesh. Life in sequence ; From the bottom up ; Getting it on ; Man the defences ; Attack of the nerves -- Earth, wind and fire. Ground beneath our feet ; Shake, rattle and roll ; Earth rocks ; Wet and windy ; Stormy weather -- We have the technology. Full of energy ; Coming in waves ; Information overload ; Pedal to the metal ; It's alive -- When science goes bad. Fraud, fakery and fantasy ; Shocks and scares ; Hot enough for you? ; Apocalypse now ; Know your limits -- Science of the future. Back to the future ; A.I. ; Innerspace ; A space odyssey ; Things to come.
At head of title: Teach yourself.
Includes bibliographical references and index.
Keywords: Science; Science